2012
DOI: 10.1177/1477153512464968
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ perceptions following retrofitting of residential area outdoor lighting with LEDs

Abstract: The use of light emitting diodes (LEDs) in outdoor lighting has energy-saving potential, but users' responses to this light source are largely unknown. An intervention study in two residential areas compared conventional lighting installations (high pressure sodium in Area 1 and high pressure mercury in Area 2) to a retrofitted LED-alternative regarding residents' perceptions of quality of light, visual accessibility and danger. Moreover, energy use was calculated. Residents' (N ¼ 60) visual accessibility impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In Northern European countries in particular, it has been found that whiter or cooler light from light emitting diode (LED) light sources reduces the perceived pleasantness of lighting and its comfort quality [42,43]. Nevertheless, the adoption of modern smart designs and energy-efficient LED light sources could yield annual energy savings of about 41-76% [44]. While these energy savings have attracted considerable interest [43], research on the impact of a transition to LED-based lighting applications has primarily focused on energy reduction and the environment rather than users' experiences of such lighting.…”
Section: Outdoor Lighting and Urban Walkingmentioning
confidence: 99%
“…In Northern European countries in particular, it has been found that whiter or cooler light from light emitting diode (LED) light sources reduces the perceived pleasantness of lighting and its comfort quality [42,43]. Nevertheless, the adoption of modern smart designs and energy-efficient LED light sources could yield annual energy savings of about 41-76% [44]. While these energy savings have attracted considerable interest [43], research on the impact of a transition to LED-based lighting applications has primarily focused on energy reduction and the environment rather than users' experiences of such lighting.…”
Section: Outdoor Lighting and Urban Walkingmentioning
confidence: 99%
“…The light distribution of the spherical half-sphere can be described with great accuracy by analytical dependence: (1) where: I m -means the maximum luminous intensity directed along the axis of the LED, γ-the plane angle that defines any direction in relation to the axis of the LED.…”
Section: Photometric Characteristics Of a Semi-spherical Ledmentioning
confidence: 99%
“…Perceived outdoor lighting quality has been studied in an environmental psychological approach, e.g., [100,101] and is assumed to describe feelings of visibility and recognition, which are important aspects of feeling safe and non-threatened. However, perceptions of LED lighting compared with traditional light sources have not been studied explicitly in environmental psychology, but see Nikunen et al [102].…”
Section: Human Healthmentioning
confidence: 99%